Quality management re‐visited: a reflective review and agenda for future research - Sousa, Rui; Voss, Christopher A (Journal of Operations Management, 2002)
AbstractQuality management (QM) has become an all‐pervasive management philosophy, finding its way into most sectors of today’s business society. After the initial hype and enthusiasm, it is time to take stock of the knowledge accumulated in what is now a mature field of study and look for directions to take the field further forward. This article reflects on the mass of literature in the field, synthesizing, organizing and structuring knowledge and offering suggestions for future research. It reviews QM research organized along five main themes: the definition of QM, the definition of product quality, the impact of QM on firm performance, QM in the context of management theory and the implementation of QM. The article draws on these themes to reflect on three questions which are fundamental to re‐visit and re‐appraise QM: (i) What is QM? (ii) Is the set of practices associated with QM valid as a whole? (iii) How to implement QM in a real business setting?